Patient-reported outcomes of treatment and adverse effects following acute lymphoblastic leukemia: a low- and middle-income country cross-sectional study - Eduardo Cerello Chapchap; Nina Melo; Denise Martins; Maria Lucia Lee; Nelson Hamerschlak (Hematology, Transfusion and Cell Therapy)
Introduction: The scenario of adult patients with acute lymphoblastic leukemia treated in Brazil has not been well described yet. Methods: Four hundred patients diagnosed with acute lymphoblastic leukemia from 1981 to 2019, registered in the Brazilian lymphoma and leukemia association (ABRALE) or their caregivers were interviewed by telephone to evaluate patient-reported perceptions of diagnosis, treatment and adverse effects. Results: Overall, 203 were male with a mean age of 15.7 years and median follow-up of 6.2 years. Main presenting symptoms were fever (39 %), bleeding/ecchymosis (38 %), intense fatigue (30 %), and musculoskeletal pain (28 %). The proportion of patients diagnosed within one week of symptoms onset differed between public (17.9 %) and private healthcare (31.1 %; p-value = 0.019). Additionally, diagnostic difficulties were higher in public care: 35 % versus 22.6 % (p-value = 0.034). Only 36 patients were able to report their treatment protocols; from a list of eight reported protocols, the most common were the Brazilian Childhood Cooperative Group for Treatment of Acute Lymphoblastic Leukemia in Children (GBTLI - 10/27.8 %) and Berlin-Frankfurt-Münster (BFM - 8/22.2 %). Seventy patients (17.5 %) required treatment modification, 37.1 % due to severe adverse effects; 21.7 % received short treatment duration (≤6 months) and 16 % proceeded to allogeneic hematopoietic stem cell transplantation with 17/64 (27 %) reporting difficulties in this step, characterized as >3 months delay. Indication for transplantation was related to minimal residual disease and cranial radiotherapy; 41.7 % reported treatment-related adverse effects (range: 1–6), in particular: mood disorders (26.3 %), neurologic deficit (13.8 %), cognitive/memory impairment (12 %), and lung disease (15 %). Risk factors for adverse effects were age, indication of transplantation and living in a large city. Treatment disparities such as diagnostic and transplantation delays remain challenges in these patients. Conclusions: Urgent interventions are needed to optimize healthcare and reduce adverse effects, especially in adolescent and young adult patients.